Dissecting the molecular mechanism regulating lateral root hydropatterning - Leftley, Nicola J. (2018)
Lateral roots (LR) contribute considerably to the architecture of the root system. The hormone auxin tightly controls the regulation of LR formation in response to environmental signals. For example, roots have the ability to distinguish between wet and dry micro environments in the soil and adapt the positioning of lateral roots accordingly. This concept is referred to as LR hydropatterning and is a novel adaptive mechanism for controlling root branching. When growing vertically down an agar plate, Arabidopsis thaliana roots are also exposed to an asymmetric distribution of water that causes a meniscus to form around the primary root (PR) circumference. LRs develop preferentially on the side of the PR in contact with water, rather than the side exposed to air. My project aims to elucidate the underlying molecular mechanisms controlling this novel adaptive response. It has been revealed that the transcription factor AUXIN RESPONSE FACTOR 7 (ARF7) is essential for LR hydropatterning. In contrast to wild type, arf7 loss of function mutants do not exhibit greater LR emergence on the side of the PR in contact with moisture. Ectopic expression of ARF7 (in 35S:ARF7 arf7-1) can rescue arf7 LR hydropatterning, implying that ARF7 regulates LR hydropatterning via a post-transcriptional mechanism. One promising post-transcriptional mechanism that may control LR hydropatterning involves protein SUMOylation (a Small Ubiquitin-like Modifier), since the SUMO mutant ots1 ots2 phenocopies the arf7 LR hydropatterning defect. OTS1 and OTS2 encode nuclear localised proteases that remove SUMO from target proteins. ARF7 is a target for SUMO modification, containing several SUMOylation sites including one within its DNA binding domain. Expressing wild type ARF7 and a non-SUMOylated version in arf7 revealed that ARF7 controls LR hydropatterning via SUMOylation. This knowledge will help reveal how plants explore the soil and position LR to maximise water (and nutrient) foraging.